Analysis of Netizen Hate Narratives on TikTok Social Media: Case Study of the Food Vlogger Controversy on the @codebluuuu Account - Masita, Masita; Putri, Sri Mei Maharani; Haliq, Abdul (The Future of Education Journal, 2025)
Social media as a means of public communication has led to an increase in the phenomenon of hate speech, especially on the TikTok platform. This study was triggered by the controversy that hit the non-celebrity food vlogger account @codebluuuu, who received criticism from netizens for writing culinary reviews that were considered unethical. The purpose of this study was to find the types of hate speech, analyze the factors that caused the phenomenon to emerge, and study the social impact of the phenomenon in the context of modern digital culture. A qualitative descriptive method was used to analyze netizen comments that were collected purposively from TikTok video uploads belonging to the @codebluuuu account. To analyze the data, hate speech was put into three categories: harsh criticism, sarcasm, and provocative speech. In addition, this study investigates triggering factors such as public expectations, digital socio-cultural sensitivities, and the impact of social media algorithms. The results show that harsh criticism that attacks the creator personally is the most common type of hate speech. Followed by sarcastic sarcasm and provocative speech that triggers collective reactions. These speeches affect a person's reputation in addition to instilling public stigma and encouraging cancel culture practices. This phenomenon shows that social control has turned into instant collective digital punishment. According to this study, hate speech in food reviews on social media is a reflection of broader social dynamics in digital society rather than just individual expression. Consequently, to use virtual public spaces morally and responsibly, a strong critical understanding and digital literacy are needed.